TINJAUAN HUKUM ISLAM TERHADAP AKAD PADA USAHA PEMANCINGAN IKAN DI DESA SENDANG KECAMATAN JAMBON KABUPATEN PONOROGO - Jarmi Pramita Sari; H. Kadenun (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
The background of the writing of this article was the practice of two contract systems in fishing that occurred in Sendang Village, Jambon District, Ponorogo Regency. The problem is the lack of clarity of the contract on the fishing. The purposes of writing this article are as follows: (1) To find out the contract used in the fishing business in Sendang Village, Jambon District, Ponorogo Regency? (2) To find out the review of Islamic law on contracts used for fishing in Sendang Village, Jambon District, Ponorogo Regency? This research was conducted qualitatively in fishing in Sendang Village, Jambon District, Ponorogo Regency, with data collection procedures through observation, interviews, and documentation techniques. The data collected related to the contract used in fishing was analyzed descriptively qualitatively using the concepts provided by Miles and Huberman which included data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, it can be said that: 1) In terms of implementation, the contract for fishing in Sendang Village, Jambon District, Ponorogo Regency is not using a sale and purchase contract or a lease contract, but the contract used for fishing in the village is by using unnamed contract (al-'uqūd gha alr al-musamma). This unnamed contract is a mixture of a lease contract and a sale and purchase contract, but the contract is more inclined to the lease contract. 2) In terms of a review of Islamic law, the contract used in the contract is allowed, because the contract is carried out on a voluntary basis without containing an element of coercion. And the contract carried out also brings benefits to both parties to the contract. As for the fishing owner, the benefit from the contract is that the pool owner gets money for the fishing business. The benefits for anglers are that they can satisfy themselves (there is a sense of satisfaction in their hearts) to fish.